REVIEW OF COASTAL CHARACTERISTICS OF IRON SAND DEPOSITS IN CILACAP CENTRAL JAVA - Hananto Kurnio (Bulletin of the Marine Geology, 2017)
Mineable iron sand deposits in Cilacap â€“ southern coastal area of Central Java have certain coastal characteristics that need to be studied in order to understand its depositional environment. With the knowledge of such environment, it can be applied to look for other places prospective of iron sand deposits that have the same characteristics especially recently when Cilacapâ€™s deposits were almost depleted. Coastal characteristics of iron sand deposit in Cilacap is shown by successive sandy beach ridges separated by marshy valleys typical of prograded coasts and by dunes of sand elongated parallel to the shore line with elevation varies from 0 m to 15 m above sea level. The iron sand deposit was derived from denudation of andesite and â€œOld Andesite Formationâ€ enriched in magnetite and ilmenite minerals in the steep elevated and deeply weathered rock hinterlands of Cilacap. High sediment loads of Serayu Basin in the hinterland (3,500-4,500 ton/km2/year; Citarum River basin only 800-1,200 ton/km2/year) was causing extensive deposition of iron sand in the coastal zone.